2017
DOI: 10.1016/j.vaccine.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Lethal factor antibodies contribute to lethal toxin neutralization in recipients of anthrax vaccine precipitated

Abstract: A major difference between two currently licensed anthrax vaccines is presence (United Kingdom Anthrax Vaccine Precipitated, AVP) or absence (United States Anthrax Vaccine Adsorbed, AVA) of quantifiable amounts of the Lethal Toxin (LT) component Lethal Factor (LF). The primary immunogen in both vaccine formulations is Protective Antigen (PA), and LT-neutralizing antibodies directed to PA are an accepted correlate of vaccine efficacy; however, vaccination studies in animal models have demonstrated that LF antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
1
18
2
1
Order By: Relevance
“…The actual concentration of EF in AVP is unclear but is lower than that of LF (26). In contrast to the present results, we recently showed that LF antibodies in AVP vaccinees contribute to LT neutralization (29). As LF is present in AVP at a concentration of approximately 1.9 g/ml (26), we suggest that this should be the minimum amount of EF or its derivative that should accompany recombinant PA in any future studies investigating the capacity of EF to enhance recombinant PA vaccines.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The actual concentration of EF in AVP is unclear but is lower than that of LF (26). In contrast to the present results, we recently showed that LF antibodies in AVP vaccinees contribute to LT neutralization (29). As LF is present in AVP at a concentration of approximately 1.9 g/ml (26), we suggest that this should be the minimum amount of EF or its derivative that should accompany recombinant PA in any future studies investigating the capacity of EF to enhance recombinant PA vaccines.…”
Section: Discussioncontrasting
confidence: 99%
“…The marginal effect of gender on ET neutralization in response to AVP reflected interaction with PA IgG concentration, where changes in PA antibody concentration resulted in detectably larger changes in ET neutralization in females than males. In contrast to our recent report noting a selective association between LF titers and LT neutralization in female recipients of AVP (29), no interaction between gender and EF IgG response in the outcome of ET neutralization in AVP recipients was detected. In contrast, gender significantly impacted the AVA response, with ET neutralization being higher in males than females.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Since naturally occurring inhalation anthrax is extremely rare, there have been safety and immunogenicity profiles of the anthrax vaccine in humans, 97 but the efficacy has only been tested in animal models, and not in clinical trials. [98][99][100] The current anthrax vaccine is made from culture filtrates of a toxigenic, avirulent, nonencapsulated mutant of the Bacillus anthracis Vollum strain, and is administered in five intramuscular doses, followed by annual boosters. The protective, antigen specific memory B cells persist for many years after vaccination and are associated with humoral immunity.…”
Section: Protection Of Health-care Workers During Infectious Disease mentioning
confidence: 99%